Ж.ИЗБАСҚАНОВ ПОЭЗИЯСЫНДА ТЕҢЕЎЛЕРДИҢ СТИЛЛИК ҚОЛЛАНЫЛЫЎЫ - Қазымбетова, З.М. (FAN va JAMIYAT, 2020)
"Linguistic poetics" as a new branch of philological sciences, studying the language of fiction, was introduced by our philologists. The poetic language of the work of art are interested everyone, the main subject of the study of modern linguistic poetics. The full context, word and image, images, aesthetic consciousness - all this helps to make the author’s point of view attractive.